Konversi Pati Sorgum Menjadi Bioetanol Menggunakan Variasi Konsentrasi Enzim Stargen tm 002 Dan Yeast Saccharomyces Cerevisiae Dengan Proses Sakarifikasi Dan Fermentasi Serentak - Ilham Ilham; Chairul Chairul; Yelmida Azis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Sorghum is a resource of grain yield with 55-75% starch composition similar to corn, that was potential as raw material for production of bio ethanol. Research based sorghum bio ethanol manufacture carried out using enzymes stargenTM 002 and starch raw materials. The purpose of this study was to determine the concentration of substrate and the best time of fermentation to produce bio ethanol. The research method consists of hydrolysis and saccharification processes are aided by enzymes stargenTM 002 followed by a fermentation process using yeast Saccaromyces Cerevisiae, ferment at room temperature, pH 4.5, enzymes stargenTM 002 concentration 2,5% and evaporated at a temperature 1000C. Using enzyme concentration were 4%, 5%, 6% and 7%, particle size used was 60-80 mesh and time of fermentation 30, 36, 42, 48, 54, 60, 66 and 72 hours. At 6% concentration of enzyme and the optimum time is 60 hours can produce the highest bio ethanol concentration of 12.413% (v/v).Keyword: Bioethanol, Enzym StargenTM 002, Fermentation, Sorghum, Substract Concentrations.